ANALISIS HUBUNGAN KARAKTERISTIK KUALITAS AUDIT TERHADAP MANAJEMEN SKANDAL KORUPSI DAN HUKUM - Indah Permata Sari (2021)
This research aims to examine the probability of audit quality characteristics that consist of audit size, audit opinion, auditor change, audit tenure, and audit fee. The control variables in this study is firm size, leverage, book-to-market, profitability, SOE, sector and year control. The sample in this study is companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2019 period. The sampling technique that used is purposive sampling and collected 469 samples. Testing the hypotesis in this study used Multinomial Logistic Regression analysis using STATA version 12. The result of this study show that audit opinion has a significant effect on scandal management of corruption and legal. Audit size, auditor change, audit tenure, and audit fee has no effect on scandal management of corruption and legal.